RoboSTEAM project the pilot phases - Conde, Miguel Ángel (2022)
Digital society demands very qualified professionals ready to this environment challenges. This makes necessary to foster the development of competences related to such context such as Computational Thinking or STEAM related skills. However, this is not an easy task, especially because integrating subjects that covers the necessary topics and competences. New active pedagogical approaches are required and this what RoboSTEAM project provides. The application of Challenge Based Learning and Physical Devices and Robotics facilitate the so named twenty first century skills. The project has been developed by several universities and schools and one of most critical parts was testing the methodology and tools, this was done into pilot phases that are described in the present work. The results show that there are important differences between partners socioeconomical context, but that the outcomes of the project are flexible enough to be applied successfully in any of them.